Determination of Teaching Aids and Methods to Inculcate Thinking Skills in History Subjects - Ahmad, Abdul Razaq (ASPENSI in Bandung, Indonesia, 2014)
ABSTRACT: This study was aimed to examine how teachers manipulate teaching methods and materials to develop historical thinking process, to make the lesson meaningful for the students, and to increase their awareness of the events studied. This is a survey by using questionnaire as the research instrument to identify knowledge and the implementation of thinking approach for the history lesson through the use of certain methods and teaching aids. The sample consisted of 56 randomly selected teachers from secondary schools in the Kinta Valley, Ipoh, Perak, Malaysia, involving 39 history option teachers (69.6%) and 17 non-option teachers (30.4%). For the aspect of teaching experience, 27 (48.2%) teachers had 1 to 9 years of experience, while 29 (51.8%) teachers have taught more than 10 years. Teachers have Â knowledge on the elements of historical thinking and commitment to inculcate the thinking elements through questioning methods and techniques, discussion, inquiry, and systematic exploration of the historical information to find cause and effect, chronology of events, and rationalization. Pictures or portraits were also analyzed and interpreted by the history teachers. Findings show that option teachers have better thinking skills and better applications than non-option teachers. In addition, option teachers also have a better and Â more systematic teaching plan through the use ofÂ greater teaching methods and aids. Â KEY WORDS: Value and history lesson, historical thinking, teachers of secondary school, methods and teaching aids, and systematic teaching.About the Author: Assoc. Prof. Dato Dr. Haji Abdul Razaq Ahmad is a Lecturer at the Faculty of Education UKM (National University of Malaysia), Campus of UKM Bangi, Selangor Darul Ehsan, Malaysia. For academic interests, he can be contacted via his e-mail at: razaq@ukm.edu.myHow to cite this article? Ahmad, Abdul Razaq. (2014). âDetermination of Teaching Aids and Methods to Inculcate Thinking Skills in History Subjectsâ in TAWARIKH: International Journal for Historical Studies, Vol.6(1) October, pp.1-12. Bandung, Indonesia: Minda Masagi Press and UNHAS Makassar, ISSN 2085-0980. Chronicle of the article: Accepted (August 28, 2014); Revised (September 27, 2014); and Published (October 28, 2014).